Semaglutide in the treatment of a patient with type 2 diabetes mellitus, psoriasis, and metabolic dysfunction-associated steatotic liver disease: a case report - Lin, Bingting; Huang, Qiuxiang; Weng, Liang; Lin, Lu (Frontiers in Medicine, 2025)
This case report highlights the therapeutic efficacy of semaglutide in a 49-year-old male with concurrent type 2 diabetes mellitus (T2DM), psoriasis (PASI 22), and metabolic dysfunction-associated steatotic liver disease (MASLD). The patient presented with metabolic dysregulation, severe psoriatic lesions, and hepatic steatosis. Initial therapies, including acitretin and topical agents, failed to yield clinical improvement. Semaglutide was initiated at 0.25 mg/week, titrated to 1 mg/week over 12 weeks, alongside metformin dose adjustment. At 24 weeks, the patient exhibited significant improvements: HbA1c decreased from 9.8 to 7.2%, body weight reduced by 6 kg, liver enzymes returned to normal ranges, and PASI declined to 6.2. Treatment was well-tolerated with no severe adverse events.